The Flood Analysis with HEC-RAS a Case Study of Muarojambi River Basin - Rury Rofyan; Prasoni Agung; Abdul Chalid (Jurnal Teknik Sipil dan Perencanaan, 2024)
This study aims to determine how wide the catchment area is on the Melayu and Jambi rivers, how much the planned flood discharge is at a return period of 2, 5, 10, 25, and 50 years with the Nakayasu Synthetic Unit Hydrograph (SUH) Analyze the water level of these rivers downstream at the planned flood discharge conditions due to backwater from the Jambi river. This also plans the cross-sectional area and length of the Jambi River as a new channel to the Batanghari River using the HECRAS model. The result shows that the Melayu River can still serve a water level of 10 for a 10-year return period and the Jambi River with a water level of 25 for a 25-year return period. However, there is a need for normalization of both rivers and disposal in a large basin located 2 km from the Melayu River. The length of the new channel section as a connection to the Batanghari River as a final water channel is 1,060 meters long, 5 meters wide at the top, 3 meters wide at the bottom of the river, with a depth of 5 m, with a channel embankment using an earthen wall.